Isolated Intraspinal Neurenteric Cyst, Mimicking Arachnoid Cyst: A Case Report - Koirala, Puspa Raj; Phuyal, Suman; Sedain, Gopal; Shilpakar, Sushil Krishna (Nepal Journal of Neuroscience, 2019)
Neurenteric cysts account for 0.7-1.3% of spinal axis tumors. These uncommon lesions results from the inappropriate partitioning of the embryonic notochordal plate and presumptive endoderm during the third week of human development. Heterotopic nests of epithelium reminiscent of gastrointestinal and respiratory tissue lead to eventual formation of compressive cystic lesions of the pediatric and adult spine. We report a 40-year-old male  presenting with slow-progressive myelopathic manifestation and ovoid non-enhancing cysticintradural extramedullary lesion at C7 level on MRI, mimicking intraspinal arachnoid cyst, who underwent successful surgical excision. The histopathological examination prove it to be neurenteric cyst.